Asymmetric Switch Costs in Numeral Naming and Number Word Reading: Implications for Models of Bilingual Language Production - Reynolds, Michael G.; Schlöffel, Sophie; Peressotti, Francesca (Frontiers in Psychology, 2016)
One approach used to gain insight into the processes underlying bilingual language comprehension and production examines the costs that arise from switching languages. For unbalanced bilinguals, asymmetric switch costs are reported in speech production, where the switch cost for L1 is larger than the switch cost for L2, whereas, symmetric switch costs are reported in language comprehension tasks, where the cost of switching is the same for L1 and L2. Presently, it is unclear why asymmetric switch costs are observed in speech production, but not in language comprehension. Three experiments are reported that simultaneously examine methodological explanations of task related differences in the switch cost asymmetry and the predictions of three accounts of the switch cost asymmetry in speech production. The results of these experiments suggest that (1) the type of language task (comprehension vs. production) determines whether an asymmetric switch cost is observed and (2) at least some of the switch cost asymmetry arises within the language system.